Biogeochemical model of nitrogen cycling in Ahe (French Polynesia), a South Pacific coral atoll with pearl farming. (August 2021) - Seceh, C.; Pinazo, C.; Rodier, M.; Lajaunie-Salla, K.; Mazoyer, C.; Grenz, C.; Le Gendre, R.
Abstract: A biogeochemical model (ECO3M-Atoll) was configured to simulate the lower food web in Ahe Atoll lagoon where phytoplankton is mostly nitrogen limited. Understanding the dynamics of phytoplankton – the main food source for oysters – is crucial for the management and the allocation of new pearl farming sites. After parametrizing the model with in situ observations, we tested different hypotheses about nitrogen cycling (benthic remineralization, atmospheric N fixation, etc. ) and compared the results to a large observational dataset. Model results show that simulated (pico- and nano-) phytoplankton biomass and nitrogen concentrations are close to in situ data. The simulated biogeochemical processes (uptake and primary production) are also very similar to the observed values. In the model, primary production ranged from 1.00 to 2.00 mg C m −3 h −1 for pico- and 0.40 to 1.00 mg C m −3 h −1 for nanophytoplankton; mean N uptake was 2.02 μmol N m −3 h −1 for pico- and 1.25 μmol N m −3 h −1 for nanophytoplankton. Highlights: A biogeochemical model was built for the Ahe Atoll. Model results and in situ data are in the same range of values. Modelling is a good tool for investigate nitrogen cycling in atolls.